Strategi Guru dalam Menerapkan Model Pembelajaran berbasis Proyek untuk Menumbuhkan Kemandirian Belajar - Jean Anggun Monoarfa; Yulanti S Mooduto; Nursyaidah (Transbahasa, 2026)
This study aims to describe teachers’ strategies in implementing Project-Based Learning (PjBL) and its role in fostering students’ independent learning at SDN 10 Limboto. This research employed a qualitative descriptive approach. The research subjects consisted of the principal, classroom teacher, and students. Data were collected through observation, interviews, and documentation. Data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing, with data validity ensured through source, technique, and time triangulation. The findings indicate that teachers implement PjBL through several stages, including defining driving questions, project planning, scheduling, project implementation, monitoring and guidance, presentation, and evaluation and reflection. Each stage contributes to the development of students’ independent learning, as reflected in increased initiative, responsibility, time management skills, and self-confidence in completing project tasks. However, the effectiveness of PjBL is strongly influenced by the teacher’s role as a facilitator, particularly in providing appropriate and gradual scaffolding. Therefore, the proper implementation of PjBL strategies can serve as an effective approach to enhance students’ independent learning in primary education.